2020
DOI: 10.1021/acsami.0c17579
|View full text |Cite
|
Sign up to set email alerts
|

Ceria Nanozymes with Preferential Renal Uptake for Acute Kidney Injury Alleviation

Abstract: Rhabdomyolysis-induced acute kidney injury (AKI) is closely related to abundant reactive oxygen species (ROS). Owing to the multi-enzymatic activity and broad-spectrum ROS scavenging capacity of ceria nanoparticles (ceria NPs), herein, we report ultrasmall citric acid modified ceria nanozymes (3−4 nm) as antioxidants to alleviate rhabdomyolysis-induced AKI through removing excessive ROS. The as-prepared ceria NPs exhibited multi-enzymatic properties such as peroxidase, catalase, and superoxide dismutase, offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 36 publications
(51 reference statements)
1
57
0
Order By: Relevance
“…In recent years, nanotechnology has been increasingly applied to the biomedical field [ 36 ], especially nanomaterials for ROS scavenging [ 37 ]. Among them, ceria nanoparticles are rich in enzymatic activity and capable of scavenging a wide range of ROS that have been widely explored [ 38 ]. The surface Ce 3+ /Ce 4+ coexistence of ceria nanoparticles, mainly produced in the tetravalent state, is mainly produced responsible for scavenging H 2 O 2 and hydroxyl radicals, and the trivalent state scavenges superoxide radicals [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nanotechnology has been increasingly applied to the biomedical field [ 36 ], especially nanomaterials for ROS scavenging [ 37 ]. Among them, ceria nanoparticles are rich in enzymatic activity and capable of scavenging a wide range of ROS that have been widely explored [ 38 ]. The surface Ce 3+ /Ce 4+ coexistence of ceria nanoparticles, mainly produced in the tetravalent state, is mainly produced responsible for scavenging H 2 O 2 and hydroxyl radicals, and the trivalent state scavenges superoxide radicals [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…AKI in mice was significantly alleviated due to the antioxidant activity of RuO 2 ( Loynachan et al, 2019 ). Similar ceria-based nanoparticles were developed by Zhang et al, 2020 Desirable results were obtained for rhabdomyolysis-induced AKI due to the ultrasmall size and multi-enzymatic properties of the nanozyme ( Liu et al, 2020b ). Apart from AKI, ultrasmall nanozymes may be used to treat other ROS-associated diseases due to their rapid renal clearance and biocompatibility.…”
Section: Nanozyme-based Treatment Of Inflammationmentioning
confidence: 89%
“…Apart from AKI, ultrasmall nanozymes may be used to treat other ROS-associated diseases due to their rapid renal clearance and biocompatibility. Liu et al (2020c) reported an ultrasmall-sized Cu 5.4 O nanozyme exhibiting broad-spectrum ROS-eliminating effect to treat AKI, acute liver injury (ALI), and wound healing ( Zhang et al, 2020 ). The transcriptomics analysis revealed that the nanozyme upregulated the oxidative stress-related genes, subsequently activated the MAPK signaling pathway, and alleviated AKI.…”
Section: Nanozyme-based Treatment Of Inflammationmentioning
confidence: 99%
“…Ceria has been successfully used in vivo to prevent oxidative damage. [44][45][46] If there exists an interchange between the bidirectional functions of ceria NPs, one must investigate these properties to get a better understanding of their physiological activities.…”
Section: Introductionmentioning
confidence: 99%